The matter of dust in Renaissance literature - Neanon, C (2020)
This thesis investigates the paradox of Renaissance dust and its poetics. It examines how the seemingly insignificant matter of dust - the least of substances, barely visible, mundane and base - was considered by contemporary theology, anthropology, and natural philosophy to be intrinsic to mankind’s existence: how it figured as the very stuff from which man’s body was made, and into which it would disintegrate at death; how it was equivalent to the atoms which some theories of matter posited as the basis of the cosmos; and how in theology – especially Reformed theology – man’s dusty nature was both the root and result of sin, and a prompt to constant contemplation of human humility. It argues that it was this kind of dust that artistically engaged writers of the period, generating what this study will call a poetics of dust.